New Zealand : 2008 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2008)
New Zealand has experienced a decade-long robust economic expansion, owing to its sound macroeconomic policies and structural reforms, but resource constraints have emerged. Executive Directors welcomed the policy settings, supported by the anticipated evolution of external and global developments. They noted that fiscal policy and tightened stance of monetary policy are appropriate. Directors noted that the financial sector remains sound. They also welcomed the steps taken by the Reserve Bank of New Zealand (RBNZ) to review its liquidity policy for banks to encourage the diversification of funding sources.